(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the cooperation of archives of Uzbekistan with the countries of the CIS and far abroad in the field of archiving in the years of independence. On the basis of concrete factual material, the authors reveal relations of archival institutions of our republic with foreign partners and show their positive results